ANALISIS RANTAI PASOK TELUR AYAM RAS CV SADAK DI KECAMATAN SUMBAWA - Putri Ayudiya Salsabillah; Muhammad Aries Zukhri Angkasa; Syahdi Mastar; Nila Wijayanti; Alia Wartiningsih (Alia Wartiningsih, M.Si, 2026)
The purpose of this study was to analyze the flow of information, financial flows, and product flows in the broiler chicken egg supply chain at CV Sadak in Sumbawa District. The location was selected purposively. Respondents were determined using a snowball sampling technique, involving the owner of CV Sadak as the primary informant, followed by input providers (dayold chicks, feed, medicines, and vitamins), middlemen, retailers, and end consumers. The research method used was descriptive, with data collection through observation, interviews, and documentation. The results indicate that the product flow begins with input providers (day-old chicks, feed, and medicines) and reaches farmers, who then distribute it to agents, retailers, and end consumers. Financial flows occur directly between farmers and input suppliers, while egg sales transactions are conducted in cash or on credit through agents and retailers. Meanwhile, the flow of information remains rudimentary and limited to direct communication between farmers, suppliers, and buyers. These findings indicate that although the supply chain is operational, strengthening information management and collaboration between stakeholders is still necessary to achieve efficiency and business sustainability.